2018
DOI: 10.1128/jb.00622-17
|View full text |Cite
|
Sign up to set email alerts
|

OxyR-Dependent Transcription Response of Sinorhizobium meliloti to Oxidative Stress

Abstract: Reactive oxygen species such as peroxides play an important role in plant development, cell wall maturation, and defense responses. During nodulation with the host plant , cells are exposed to HO in infection threads and developing nodules (R. Santos, D. Hérouart, S. Sigaud, D. Touati, and A. Puppo, Mol Plant Microbe Interact 14:86-89, 2001, https://doi.org/10.1094/MPMI.2001.14.1.86). cells likely also experience oxidative stress, from both internal and external sources, during life in the soil. Here, we prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 62 publications
1
15
0
Order By: Relevance
“…We then showed that hslUV transcription was induced by low temperature and high NaCl stress and to lesser extent by treatment with H 2 O 2 . A recent mRNA microarray experiment following H 2 O 2 treatment showed signal log ratios of 2.1 and 1.8 for hslU and hslV, respectively, which is in rough agreement with our findings (32). Furthermore, we showed that clpXP1 expression was repressed by treatment with low concentrations of the aminoglycoside antibiotic neomycin, which was expected to increase the frequency of amino acid misincorporation and thereby alter protein stability (33).…”
Section: Discussionsupporting
confidence: 91%
“…We then showed that hslUV transcription was induced by low temperature and high NaCl stress and to lesser extent by treatment with H 2 O 2 . A recent mRNA microarray experiment following H 2 O 2 treatment showed signal log ratios of 2.1 and 1.8 for hslU and hslV, respectively, which is in rough agreement with our findings (32). Furthermore, we showed that clpXP1 expression was repressed by treatment with low concentrations of the aminoglycoside antibiotic neomycin, which was expected to increase the frequency of amino acid misincorporation and thereby alter protein stability (33).…”
Section: Discussionsupporting
confidence: 91%
“…RpoH. Sme RpoH1 and RpoH2 alternative sigma factors mediate response to various stressors, including heat, acid, hydrogen peroxide, stationary phase growth, and envelope disrupting agents (30)(31)(32)(33). CLas RpoH is most similar to Sme RpoH1 (72% identity), which is required for an effective nitrogen-fixing symbiosis (32,34).…”
Section: Resultsmentioning
confidence: 99%
“…In Escherichia coli, PAs also combat oxidative stress by preventing DNA damage and increasing the expression of the genes for catalase (katG) and its transcriptional activator oxyR [3,44]. OxyR is well conserved in proteobacteria such as S. meliloti, where it regulates the expression of the catalase gene katA, the product of which is essential for counteracting oxidative stress [45,46]. Catalase activity assays of extracts of cells exposed to H 2 O 2 shock (2 mM) revealed no differences between the Rm8530 odc2 mutant and the wild-type (data not shown).…”
Section: Discussionmentioning
confidence: 99%